1992
DOI: 10.3758/bf03212247
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the intelligibility of speech through multiple phonemic restorations

Abstract: Outside ofthe laboratory, listening conditions are often less than ideal, and when attending to sounds from a particular source, portions are often obliterated by extraneous noises. However, listeners possess rather elegant reconstructive mechanisms. Restoration can be complete, so that missing segments are indistinguishable from those actually present and the listener is unaware that the signal is fragmented. This phenomenon, called temporal induction (TD, has been studied extensively with nonverbal signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 30 publications
8
103
0
Order By: Relevance
“…Each mean was based on data pooled between the two testing Fig. 2(a)], the intelligibility of the interrupted speech was higher when the interrupted gaps are filled with noise (filled circles) relative to silence (open circles) [F (1, 11) ¼ 104.79, p < 0.0001, M se ¼ 12.943], which is consistent with previous demonstrations of the phonemic restoration effect (Bashford et al, 1992;Shinn-Cunningham and Wang, 2007). In addition, intelligibility was found to increase as the interruption rate increased [F(2, 22) ¼ 89.90, p < 0.0001, M se ¼ 9.44], presumably due to the shorter duration of the interruption intervals at higher interruption rates.…”
Section: Scoringsupporting
confidence: 78%
See 2 more Smart Citations
“…Each mean was based on data pooled between the two testing Fig. 2(a)], the intelligibility of the interrupted speech was higher when the interrupted gaps are filled with noise (filled circles) relative to silence (open circles) [F (1, 11) ¼ 104.79, p < 0.0001, M se ¼ 12.943], which is consistent with previous demonstrations of the phonemic restoration effect (Bashford et al, 1992;Shinn-Cunningham and Wang, 2007). In addition, intelligibility was found to increase as the interruption rate increased [F(2, 22) ¼ 89.90, p < 0.0001, M se ¼ 9.44], presumably due to the shorter duration of the interruption intervals at higher interruption rates.…”
Section: Scoringsupporting
confidence: 78%
“…Because past studies of phonemic restoration effects with similar silent intervals resulted in decreased speech intelligibility (Bashford et al, 1992;Shinn-Cunningham and Wang, 2007), the notion that interruptions to the at-the-ear signal are in some sense implausible under natural listening conditions may contribute to the phonemic restoration effect. It is also important to note that the noise interruptions appear to be unaffected by the room manipulation, as evidenced by the lack of a significant difference in intelligibility performance between the two room conditions (Pre-vs Post-Room) [t(35) ¼ 1.732, M se ¼ 1.33126, p ¼ 0.092].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies has been undertaken to test the validity of this suggestion. These studies have found that, in keeping with the spectral requirements for nonverbal auditory induction, the greatest increase in apparent continuity of narrowband speech passages interrupted periodically by narrowband noise occurred when the center frequencies of the speech and noise bands were the same (Bashford & Warren, 1979, 1987, and also that the intelligibility of narrowband sentences was greatest when the interrupting noise bands matched the center frequency of the speech (Bashford et al, 1992). Bregman (1990) has suggested that phonemic restoration represents a "schema-driven stream segregation" that is fundamentally different from the auditory induction of nonverbal sounds such as tones and noises.…”
Section: Methodsmentioning
confidence: 99%
“…Perceptual restoration studies indicate that the restoration effect depends on acoustic cues that relate to the additive noise (Powers and Wilcox, 1977;Samuel, 1981;Warren et al, 1997) and context cues that relate to the speech material (Warren and Sherman, 1974;Verschuure and Brocaar, 1983;Bashford et al, 1992). The current section describes the stimuli and evaluation metric used in the present work.…”
Section: Perceptual Restoration Taskmentioning
confidence: 99%